1978
DOI: 10.1346/ccmn.1978.0260207
|View full text |Cite
|
Sign up to set email alerts
|

The Ordering of Cetylpyridinium Bromide on Vermiculite

Abstract: X-ray superlattice reflections, infrared spectroscopy, and chemical analyses have established that cetylpyridinium bromide (CPB) is highly ordered when adsorbed on vermiculite. The molecules, which stand at about 57 ~ to the silicate surface, form close-packed arrays. Full surface coverage is achieved only for the most highly charged vermiculites. The packing within the arrays accounted for the superlattice observed and each adsorbed molecule had an area of 18.4 /~2 at the surface. The implications of these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 22 publications
2
21
0
3
Order By: Relevance
“…On the external surfaces of non-expanding minerals such as kaolinite, a bilayer formed at maximum coverage, with each adsorbed molecule or ion having a mean coverage of 0.27 nm 2. These results were confirmed by Slade et al (1978), who concluded that the CPB molecules formed closepacked arrays oriented at 57* to the internal silicate surfaces.…”
Section: Introductionsupporting
confidence: 60%
“…On the external surfaces of non-expanding minerals such as kaolinite, a bilayer formed at maximum coverage, with each adsorbed molecule or ion having a mean coverage of 0.27 nm 2. These results were confirmed by Slade et al (1978), who concluded that the CPB molecules formed closepacked arrays oriented at 57* to the internal silicate surfaces.…”
Section: Introductionsupporting
confidence: 60%
“…Previous workers have chiefly been concerned with the various charged species and radicals formed by benzidine when it is intercalated between clay layers, however, the structures of such intercalates are generally not known. As part of a program concerned with the structures of clay-organic intercalates (Slade et al, 1978;Raupach et al, 1979), we report here the partial structure of a black intercalate formed by vermiculite with benzidine hydrochloride in an aqueous solution at pH 1.6.…”
Section: Introductionmentioning
confidence: 98%
“…The application of the polarized ATR technique has been shown to be useful for deducing the orientation of intercalated species on phyllosilicates, including cetylpyridinium cations, which have also been used for surface area measurements (Slade et al, 1978), amino acids (Raupach et al, 1975;Raupach and Janik, 1976), and paraquat (Raupach et al, 1979).…”
Section: Introductionmentioning
confidence: 99%